Changing Perspectives: Should We Integrate Pharmacology in the Clinical Phase? - Umar, Badar Uddin; Haque, Mainul (Bangladesh Journal of Medical Science, 2022)
Medical education has gone through tremendous evolution over the last few centuries. In the pre-Flexner and Osler era, medical education was mainly an apprenticeship-based model. After Flexner’s report in 1910, medical schools were more formalized in the West and became affiliated with universities. They ran four-year undergraduate courses comprising 2 years in preclinical basic science and two years in the clinical phase. Many other countries followed the British model, with five years of undergraduate training and one year of intensive internship training in the hospital. These knowledge-laden, didactic, teacher-centered courses could not produce skilled physicians to meet the challenges and health care needs of the 21st century. That is why innovative teaching methodologies were introduced in medical schools. Problembased learning, team-based learning, flipped classrooms, and integrated curriculum concepts were introduced. In Bangladesh, the medical education also going through a similar transition and heading towards an integrated medical curriculum. Pharmacology being a core preclinical science, is, in fact, at the cusps of clinical education. To produce competent physicians with good prescribing competency, knowledge of drugs is essential. In this perspective, pharmacology is a unique subject that should be integrated across all phases of medical education. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 249-261